The Management of Human Resources Development in Increasing the Quality of Islamic Education Institutions - Rahmi, Elvi; Patoni, Achmad; Sulistyorini, Sulistyorini (AT-TA'LIM, 2020)
Human resources are the biggest strength in the management of Islamic educational institutions. The quality of human resources is crucial right now, because competence of human resources who have knowledge and skills will be able to cope environmental changes. Teachers and employees are the key of success in educational institutions. Good or bad performance of teachers and employees will support the competitiveness of schools. Based on this phenomenon, this research reveals the development of educators and education staff in enhancing competitiveness in the Excellent Islamic Elementary School in Bukittinggi City. This research uses descriptive qualitative. Located in Excellent Islamic Elementary School Bukittinggi City. The source of data in this study is the board of trustees, principals, teachers and employees. The techniques of data collection are participant observation, in-depth interviews and documentation. Later on the collected data is analyzed using data reduction techniques, data presentation, and conclusion. All data are approved by validity through a credibility test, transferability test, dependability test and conformability test. The results showed that the development of teachers and employees is done through 1) on the job training, that is, development that takes place during working hours takes place both formally and informally. 2) Off the job training, that is development that has done specifically outside of work. As for the development carried out: a) training in the form of quantum teaching training, workshops for making learning media and parenting seminars, b) rotation position, c) Religious Development, d) Teacher working groups (KKG) and comparative studies. This development aims to improve the competencies of teachers and employees in the school environment so that they can improve the quality of Islamic educational institutions in accordance with the increasingly stringent times.Â